The Effect of Questioning the Author Strategy on EFL Preparatory School Students’ Achievement in Literature Focus - Nadeem, Moayad Mahmood; Muhammed , Ibtisam J. (Journal of Tikrit University for Humanities, 2025)
Questioning the Author Strategy (henceforth: QTA) gets the student the ability to think about the author’s ideas and meaning that appear in the real text, and this strategy focuses on a series of questions that are asked by the student naturally . This study aims at finding out the effect of Questioning the Author Strategy on the EFL preparatory school students‘ achievement in learning literature focus ; finding out the effect of (QTA) Strategy on the experimental group’s achievement at the recognition and production levels. These aims have been achieved through verifying the following hypotheses: There is no statistically significant difference between the mean scores of the experimental group which is taught by using (QTA) Strategy and the mean scores of the control group which is taught according to the communicative method; There is no statistically significant difference in the mean scores between the recognition and production levels of the experimental group in the posttest. The sample of this study is (60) students have been randomly selected from the Iraqi EFL fourth preparatory school students in Kirkuk city, Al Huda School for girls during the academic year (2024-2025), and has been divided into two equal groups, i.e. the experimental and control groups. The two groups have been taught by the researcher himself .The experimental group has been taught according to (QTA) Strategy, while the control group has been taught by using the traditional method. The results show that (QTA) has a positive effect and can be regarded as a helpful strategy in teaching literature focus.